Penerapan Arsitektur Multisensori pada Perancangan Pusat Wisata Gastronomi Tradisional Bali - Ni Made Putri Nadia Saraswati; Made Mariada Rijasa; Siluh Putu Natha Primadewi (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2025)
Abstract: The rapid growth of global culinary tourism and its significant contribution to Indonesia's creative economy have driven the design of the Bali Traditional Gastronomy Tourism Center to address the lack of local culinary options in key tourist areas like Canggu, Seminyak, and Kuta. This project aims to formulate specifications, concepts, and a spatial program using a multisensory architectural approach, supported by methods such as observation, comparative studies, and literature reviews. Based on a concept focused on recreational, innovative, and educational experiences, the design specifies a total building area of 5,658.06 m², which includes a restaurant, a cooking class, and a gallery, strategically located on Jalan Sunset Road, Seminyak, with a site area of 13,640 m². The design concept applies a radial circulation pattern, the Balinese architectural concept of natah, and the use of softscape and hardscape elements to enrich the sensory experience, ultimately creating an innovative, informative, and engaging culinary destination for visitors. Keyword: Bali Traditional Gastronomy Tourism, Multisensory Architecture, Innovative Experience. Abstrak: Pertumbuhan pesat pariwisata kuliner global dan kontribusinya yang signifikan terhadap ekonomi kreatif di Indonesia mendorong perancangan Pusat Wisata Gastronomi Tradisional Bali untuk mengatasi minimnya kuliner lokal di area wisata utama seperti Canggu,Seminyak, dan Kuta. Perancangan ini bertujuan merumuskan spesifikasi, konsep, dan program ruang dengan pendekatan arsitektur multisensori, didukung oleh metode observasi, studi banding, dan studi literatur. Dengan konsep yang berfokus pada pengalaman rekreatif, inovatif, dan edukatif, perancangan ini merumuskan total luas bangunan 5.658,06 m² yang mencakup restoran, cooking class, dan galeri, yang berlokasi strategis di Jalan Sunset Road, Seminyak, dengan luas tapak 13.640 m². Konsep perancangan menerapkan sirkulasi radial, serta konsep natah pada arsitektur Bali, serta penggunaan elemen softscape dan hardscape untuk memperkaya pengalaman indrawi, menciptakan destinasi wisata kuliner yang inovatif, informatif, dan menarik bagi pengunjung. Kata Kunci: Pariwisata Gastronomi Tradisional Bali, Arsitektur Multisensori, Pengalaman Inovatif.